Efektivitas Tugas Bawaslu Kabupaten Pekalongan dalam Mencegah Money Politic Pada Pilkada Tahun 2020 di Kecamatan Kesesi - Subekti Dwi Nur Rohmah; Akhmad Jalaludin (Manabia: Journal of Constitutional Law, 2022)
Bawaslu is an institution that has the main task and carries out supervision through the stages of holding general elections, which consist of general elections for members of the Regional Representative Council, Regional Representative Council Regional Representative Council, Presidential elections and regional head elections. Bawaslu is a permanent body, with a term of service for members of the election supervisory body which is 5 years starting from the taking of the oath of office. As a democratic country, indonesia carries out ragional head elections at the governor’s level every five years. In Central Java Province, regional head elections were held in 2020. However, the implementation of ragional head elections was marked by the existence of money politics or so-called money politics. Money politics is one of the customers in the implementation of general election. This paper aims to see the effectiveness of the implementation of Bawaslu’s duties in preventing money politics in the post-conflict local election in Central Java Province in 2020. This study uses empirical juridical research with a qualitative approach, and uses analytical techniques consisting of data reduction, data presentation and conclusion drawing. This research concludes that based on the benchmark of the effectiveness of Bawaslu in preventing the occurrence of money politics in Pekalongan Rregency, it can be said that it has not been very effective because there are still very large inhibiting factors such as low levels of economy, level of political knowledge, low society and low culture of society. Elections are very important in democracy. Like two sides of a coin that cannot be separated from each other, so are elections and democracy. The two cannot be separated if there is a general election then there is democracy. As a democratic country, indonesia carries out ragional head elections at the governor’s level every five years. In Central Java Province, regional head elections were held in 2020. However, the implementation of ragional head elections was marked by the existence of money politics or so-called money politics. Money politics is one of the customers in the implementation of general election. This paper aims to see the effectiveness of the implementation of Bawaslu’s duties in preventing money politics in the post-conflict local election in Central Java Province in 2020. This study uses empirical juridical research with a qualitative approach, and uses analytical techniques consisting of data reduction, data presentation and conclusion drawing. This research concludes that based on the benchmark of the effectiveness of Bawaslu in preventing the occurrence of money politics in Pekalongan Rregency, it can be said that it has not been very effective because there are still very large inhibiting factors such as low levels of economy, level of political knowledge, low society and low culture of society.